Celestial categories: How languages encode, structure, and transmit astronomical knowledge across cultures - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2026)
Cultural astronomy has long documented how human societies interpret celestial phenomena, yet the linguistic dimension—how languages grammatically and lexically encode astronomical knowledge—remains systematically underexplored. While the sun, moon, planets, and stars present universal perceptual experiences, languages categorize and structure these referents in highly diverse ways, with implications for cognitive science, linguistic typology, and language documentation This paper examines how languages across diverse families encode, structure, and transmit celestial knowledge. Methods: The study synthesizes evidence from five language families (Austronesian, Pama Nyungan, Mayan, Uralic, Indo European) using frameworks from linguistic relativity, semantic typology, cognitive metaphor theory, and the ethnography of communication. Data sources include descriptive grammars, ethnoastronomical literature, oral narrative recordings, and comparative historical linguistics. Celestial lexicons are organized by eight semantic dimensions (brightness, motion, periodicity, visibility pattern, shape, colour, mythological role, functional association). Grammatical systems integrate celestial referents through noun class/gender assignment (e.g., Bantu languages), numeral classifiers (e.g., Japanese lunar phase counters), evidentiality marking (e.g., Tariana obligatory source specification for eclipses), and absolute spatial frames of reference (e.g., Guugu Yimithirr solar anchored directions). Transmission occurs through parent child nighttime dialogue, oral genres (Australian Dreaming narratives, Polynesian wayfinding chants, Maya agricultural instructions), language contact (borrowing and semantic shift), and material gestural modalities (bark paintings, deictic pointing). Case studies reveal universals (sun/moon as primary anchors) alongside language specific structuring (evidential distinctions for meteors, grammatical number for auroral displays). Languages are not passive reflectors of celestial reality; they actively categorize, structure, and transmit skylore through distinct linguistic mechanisms. The findings support a moderate linguistic relativity hypothesis in the domain of natural kinds: grammatical patterns shape habitual attention to celestial phenomena without determining perception.